Development of Force and Motion Concept Self-Efficacy Inventory (FMCSEI) for Senior High School Students - Panergayo, Albert Andry E. (Jurnal Penelitian dan Pembelajaran IPA, 2023)
This study aimed to develop and validate the Force and Motion Concept Self-Efficacy Inventory (FMCSEI), a content-specific self-efficacy inventory for the senior high school level. This study involved 1361 senior high school students from the Schools Division Office of San Pablo City, Laguna. Exploratory Factor Analysis (EFA) was initiated to determine the underlying factors within the initial 39-item scale. Based on EFA, FMCSEI managed to capture three factors related to force and motion learning self-efficacy, namely: applications of knowledge of force and motion, conceptual understanding of force concept, and real-life application of Newton’s laws of motion. FMCSEI component structure obtained an excellent reliability index as revealed by the Cronbach’s alpha (>0.80). Correlation analysis among the extracted components emerged to be strongly associated which further established high internal consistency of the developed instrument.  Therefore, FMCSEI, composed of 34 items, can be utilized as a valid and reliable instrument by educators or researchers to assess the self-efficacy towards learning force and motion concept in senior high school level. This tool can provide physics teachers, useful insights in instructional planning and designing towards improved attitude and disposition of senior high students in physics courses.